A STUDY ON AGGRESSIVE BEHAVIOUR AND EMOTIONAL MATURITY OF ADOLESCENT STUDENTS - Jeba N, Mary (International Journal of Research -GRANTHAALAYAH, 2018)
The study intended to find out any relationship between aggressive behavior and emotional maturity of adolescents. Aggressive behavior is the reactionary and impulsive behaviour. The role of education is the modification of behaviour of the individual. So, school has a great role in mending the behaviour of the students. Moral education and mediation can be given to students. This may help them to get rid of the aggressive behaviour. The investigator used the mean, standard deviation, t-test and ANOVA (analysis of variance) to analyze the data and results were tabulated. The adolescent students show more aggressive behaviour than emotional maturity.